The Use of Papers in The Acehnese Islamic Manuscripts and its Historical Context - Fakhriati, Fakhriati (Center for Research and Development of Religious Literature and Heritage, 2013)
Paper is the most popular material used for writing Islamic manuscript in the Archipelago, including Aceh. Both imported and traditional papers were used for writing Islamic manuscripts in Aceh. Using certain paper for writing an Islamic manuscript might be used for tracing a great information on the context of papers that can be able to learn and know the relationship between the country of paper producers and the country of the paper users. This article argues that Acehnese Islamic manuscripts were written mostly in imported papers containing of watermark images commonly used in Islamic countries. This indicates that Acehnese had either social, economic, political, or knowledge relationship with Islamic countries.